Persepsi Remaja Perempuan pada Produk Pemutih Niacinamide - Siti Aulia Nurmedina; Dewi Sagita; Syamsul Hidayat (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to analyze adolescent girls' perceptions of skin whitening products containing niacinamide, an active ingredient known to have skin brightening and hyperpigmentation reduction benefits. This study used a quantitative approach with a survey method, involving 100 adolescent girls aged 15-21 years old in the city of Serang. Data was collected through a questionnaire that measured factors such as brand awareness, belief in product benefits, and the influence of social media in purchasing decisions. The results showed that the majority of respondents had positive perceptions of products containing niacinamide, especially regarding their safety and effectiveness. However, there are concerns regarding possible long-term side effects. Social media plays a significant role in shaping respondents' opinions through consumer reviews and influencer recommendations.